Enhancing Vocational High School Students’ Employability Skills through Training in Developing Applicant Tracking System-Compatible Resumes as a Strategy for Adapting to Digital Recruitment - Agung Zulfikri; Syifa Hanifa Salsabila; Agus Usman; Teguh Prasetio; Irvan Andirianto Prabowo (LOSARI DIGITAL, 2026)
This community service activity is designed to help students prepare for entering the workforce. The activity will teach students how to create a resume (CV) that can pass through an Applicant Tracking System (ATS), which is how companies currently screen candidates. Students from SMK AL-HASRA Depok were invited to participate in this activity, which was held at Universitas Pembangunan Jaya. The method used in this community service activity employed a practical learning approach, encompassing preparation, training, evaluation, and a final report. The results of the activity showed an improvement in participants’ skills following the training. Participants’ understanding of the Applicant Tracking System (ATS) increased from 32% to 85%, their ability to create an ATS-friendly CV improved from 25% to 88%, and their understanding of keyword usage in CVs rose from 30% to 82%. These results indicate that the training successfully enhanced participants’ employability skills in navigating the digital recruitment process. This activity also provided insights by comparing students’ work before and after the training, as well as by assessing the quality of the CVs they created. Additionally, the students felt more confident in navigating the entire digital recruitment process. This training on how to create an Applicant Tracking System (ATS)-friendly CV truly helped the students prepare themselves for job hunting. The project’s outcomes aim to establish this initiative as a model for training programs that help people adapt to the ever-changing technological landscape.